Induced convexity and the problem of the induced best approximation - Lupşa, Liana; Cristescu, Gabriela (Rev. Anal. Numér. Théor. Approx., 2001)
In this paper the problem of the "induced best approximation of an element" of an arbitrary set X by elements of an induced seg-convex subset A of X is discussed.